2011
DOI: 10.1007/s11524-010-9508-7
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative View of Drug Use Behaviors of Mexican Male Injection Drug Users Deported from the United States

Abstract: Deportees are a hidden yet highly vulnerable and numerous population. Significantly, little data exists about the substance use and deportation experiences of Mexicans deported from the United States. This pilot qualitative study describes illicit drug use behaviors among 24 Mexico-born male injection drug users (IDUs), ≥18 years old, residing in Tijuana, Mexico who self-identified as deportees from the United States. In-person interviews were conducted in Tijuana, Mexico in 2008. Content analysis of interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(100 citation statements)
references
References 31 publications
1
94
1
4
Order By: Relevance
“…Latin American migrants sent back from the US might face the stigma of being considered criminals, as people believe criminal activities to be the main cause of deportation [3,4]. Deportees who are repatriated by land through the Mexico-US border generally lack support networks in the Mexican border cities they arrive to, and they can face discrimination, human rights violations, and victimization by organized crime [3,13,14]. Given the above, deportation would be an extremely stressful experience, with foreseeable consequences on mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latin American migrants sent back from the US might face the stigma of being considered criminals, as people believe criminal activities to be the main cause of deportation [3,4]. Deportees who are repatriated by land through the Mexico-US border generally lack support networks in the Mexican border cities they arrive to, and they can face discrimination, human rights violations, and victimization by organized crime [3,13,14]. Given the above, deportation would be an extremely stressful experience, with foreseeable consequences on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Given the above, deportation would be an extremely stressful experience, with foreseeable consequences on mental health. Research conducted with Latin American migrants deported from the US has reported an increase in drug use, as a result of forced displacement and lack of social networks [13,15,16], and fear of deportation has been shown to be associated with depressive symptoms [17], but studies of this population are still scarce, and the generalizability of results is limited by the use of convenience samples and non-standardized instruments.…”
Section: Introductionmentioning
confidence: 99%
“…We found that nearly one-half of U.S. migrant FSW-IDUs were ever deported from the U.S., demonstrating that U.S. re-entry by deportees as documented by Weeks et al, 67 is also prevalent among Mexican FSW-IDUs. Deportation often imposes significant emotional and economic tolls on migrants and their families due to separation from loved ones in the U.S. 68,69 Separation from family residing in the U.S. was also reported by U.S.-migrant FSW-IDUs, which may motivate women's return to the U.S. (circular migration). Several studies of migrant Latinos have linked circular migration to HIV transmission in receiving communities.…”
Section: Discussionmentioning
confidence: 99%
“…69,75 Timely use of HIV testing services by binational migrants may be critical to containing HIV transmission in the U.S. and Mexico, 76 and is recommended among high-risk populations, including substance users. 54,71 The U.S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation